Profile of Seventh-Grade Middle School Students' Understanding of Fractions - Siva Natun; Rafiq Badjeber; Yulia Yulia (Universitas Islam Sultan Agung, 2026)
This study aims to describe seventh-grade students' understanding of fractions at SMP. This study employs a descriptive qualitative approach and a case study design, with three students as subjects classified into high, medium, and low categories. Data were collected through tests, interviews, and documentation. The study's results show that students' understanding of fractions varies. Students in the high category can explain and apply the concept of fractions effectively. Students in the medium category still have difficulty distinguishing between types of fractions, but can explain the meaning of a fraction and give everyday examples. Meanwhile, students in the low category show limited understanding of the concept, as they still have difficulty explaining fractions and are therefore unable to apply it effectively.Keywords: Fraction concepts, Conceptual understanding, Mathematics learning, Junior high school students